The Role of Islam in Shaping the Millennial Generation’s Morals and Character - Fani Putri Amaliya; Saufitri Komalasari; Masduki Asbari (Journal of Information Systems and Management (JISMA), 2022)
Islamic education is an educational system that covers all aspects of life needed by the servants of Allah. Islamic education does not adhere to a closed system but is open to the demands of the welfare of mankind, both demands in the fields of science and technology as well as demands for fulfilling the needs of spiritual life. In entering the area of ​​practical thinking, Islamic education focuses more on problems and educational processes that must be implemented in systems, patterns, and programs with various appropriate methods to achieve goals. The strategic target of Islamic education is to instill and develop religious values ​​and scientific values ​​deeply and widely in the personality of teenagers in this millennial era so that an attitude of faith and piety will be formed in them with the ability to develop knowledge in everyday life. In other terms, the goal of Islamic education is to integrate faith and piety with knowledge in the human person to realize the welfare of life in this world and happiness in the hereafter. Islamic education cannot be understood to be limited to "Islamic teaching". Because the success of Islamic education is not enough only in terms of how far the child masters things that are cognitive or knowledge of religious teachings alone but about how far these religious values ​​are embedded in the soul and how far these values ​​are manifested in behavior and behavior. the character of a teenager every day so that it can give birth to the noble character. Islamic education not only emphasizes religious teachings but must also lead to the mastery of science and other sciences and skills that will help to meet and deal with progress and changes that continue to occur. Because developing science and technology does not mean that Islamic education must abandon its role in providing the provision of religious sciences. Islamic religious education has a big role in the education system that builds the personality or character of the nation.